Digestibility and Egg Yolk Pigment Intensity of Local Ducks Fed Shrimps Head Meal, Leucaena Leaf Meal and L-Carnitine Supplementation - Widiyastuti, T; Prayitno, CH; Sudibya, Sudibya (ANIMAL PRODUCTION, 2007)
The experiment was conducted to determine the nutrient digestibility and egg yolk pigment intensity of local ducks which fed shrimps head meal, leucaena leaf meal and L-Carnitine supplement.  The experimental method used was a Completely Randomized Design (CRD) with four treatments i.e : R0 (feed with  leucaena leaf meal), R1 (feed with 25 ppm L-Carnitine supplement), R2 (feed with 2% shrimps head meal) and R3 (feed with 4% shrimps head meal). A total of  0,20% FeSO4/kg feed were supplemented to all treatments.  The results showed that L-Carnitine supplements and fed shrimps head meal  (2% and 4%) have no significant effects (P>0,05) on crude fat and crude protein  digestibility  but have significant (P<0.05) effects on yolk pigment intensity.  L-Carnitine supplements resulted in 86,69% crude fat and 90,78% crude protein digestibility).  Ducks fed with 4% shrimps head meal (R3) produced eggs with highest yolk pigment intensity (10,55). (Animal Production 9(1): 30-35 (2007) Key Words : shrimps head meal, L-Carnitine, digestibility, yolk pigment intensity